Peculiarities of Cryopreservation Influence on Structural and Functional Characteristics of Bone Marrow Ex Vivo Derived Dendritic Cells - Kisielova, Hanna; Goltsev, Anatoliy; Dubrava, Tatyana; Yampolska, Kateryna (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 289